Breaking The Curfew : A Political Journey Through Pakistan - Duncan, Emma (London Arrow Books, 1989)
This is a study of Pakistan, currently ruled by an autocratic, semi-military dictatorship, with a superpower on one border and the unstable fundamentalist regime of Iran, which plays unwilling host to 3 million Afghan refugees, on another.
Include Index
Keywords: Pakistan -- Politics and government -- Travel